Humanism: A Revolutionary Project II - Marenco Rojas, Helen (2022)
This second essay in a series of four concerning humanism as a revolutionary project examines the fourth historical blossom of humanist praxis since its origins in Classic Greece. The following text basically covers three facets of this topic: 1. A general introduction to liberal thought in the XVIIIth century and its specific significance for humanism; 2. The work of Jean-Jacques Rousseau and its humanist significance; 3. Conclusions referred to the particular theme of this article as well as its import within he series of four essays that cover the five main blossoming of humanist praxis up to our days, while in the final one we shall focus in what we have decided to term as “New Humanism Manifesto”. Thus, with this second essay we will come closer to the socialist humanism of the XIXth century (fifth blossom of humanist praxis) and in this manner we will reach the threshold of the most important of these works in which we will attempt to establish in a more advanced form the main concepts necessary for establishing a XXIst century humanism.